Odpowiedź :
Odpowiedź:
[tex]1)\ \ 4\frac{1}{7}+3\frac{1}{6}=4\frac{6}{42}+3\frac{7}{42}=7\frac{13}{42}\\\\\\2)\ \ 5\frac{1}{2}-3\frac{1}{5}=5\frac{5}{10}-3\frac{2}{10}=2\frac{3}{10}\\\\\\3)\ \ 2\frac{3}{4}\cdot1\frac{1}{22}=\frac{\not11^1}{4}\cdot\frac{23}{\not22_{2}}=\frac{23}{8}=2\frac{7}{8}\\\\\\4)\ \ 5\frac{1}{3}:2\frac{5}{6}=\frac{16}{3}:\frac{17}{6}=\frac{16}{\not3_{1}}\cdot\frac{\not6^2}{17}=\frac{32}{17}=1\frac{15}{17}[/tex]
[tex]5)\ \ 4\frac{1}{2}+1\frac{3}{5}+1\frac{3}{10}=4\frac{5}{10}+1\frac{6}{10}+1\frac{3}{10}=6\frac{14}{10}=7\frac{4}{10}=7\frac{2}{5}\\\\\\6)\ \ (11-9\frac{3}{5}):1\frac{3}{10}=(10\frac{5}{5}-9\frac{3}{5}):\frac{13}{10}=1\frac{2}{5}:\frac{13}{10}=\frac{7}{\not5_{1} }\cdot\frac{\not10^2}{13}=\frac{14}{13}=1\frac{1}{13}[/tex]
lub jeśli taki zapis
[tex](11-9\frac{3}{8}):1\frac{3}{10}=(10\frac{8}{8}-9\frac{3}{8}):\frac{13}{10}=1\frac{5}{8}:\frac{13}{10}=\frac{\not13^1}{\not8_{4}}\cdot\frac{\not10^5}{\not13_{1}}=\frac{5}{4}=1\frac{1}{4}[/tex]